A new peroxisomal disorder with fetal and neonatal adrenal insufficiency. Issue 1 (July 1994) - Vanhole, C; de Zegher, F; Casaer, P; Devlieger, H; Wanders, R J; Vanhove, G; Jaeken, J
Abstract : A boy with a new type of adrenoleukodystrophy is described. This was characterised by fetal and neonatal adrenal insufficiency, a neurological picture as seen in neonatal adrenoleukodystrophy, but with a normal number of peroxisomes in the liver and a peroxisomal dysfunction limited to the very long chain fatty acids and pristanic acid.